How the centriole builds its cilium: of mothers, daughters, and the acquisition of appendages. (February 2021) - Kumar, Dhivya; Reiter, Jeremy
Abstract : Centrioles are microtubule-based structures in eukaryotic cells. From organizing the microtubule cytoskeleton during interphase to focusing the mitotic spindle during mitosis, centrioles are busy at all stages of the cell cycle. One crucial interphase function of centrioles is to assemble cilia, microtubular projections that can either be motile or nonmotile. Motile cilia function in sperm locomotion and propulsion of extracellular fluids, as in mucus flow in the lung. Immotile primary cilia are critical for some forms of intercellular signaling. Here, we review how procentrioles mature into daughter and, then, mother centrioles. We highlight key steps in ciliogenesis, including the acquisition of appendages by the mother centriole, as well as the distal centriole, an understudied domain critical for ciliogenesis. Importantly, several genes mutated in ciliopathies encode distal centriolar components. We propose that understanding how centrioles are remodeled to support cilium assembly will provide insights into the molecular etiologies of ciliopathies.